Blood/Body Fluid Exposure and Needle Stick/Sharp Injury among Nurses Working in Public Hospitals; Southwest Ethiopia - Yeshitila Belay Belachew; Tefera Belachew Lema; Tefera Belachew Lema; Gugssa Nemera Germossa; Yohannes Mehretie Adinew (Frontiers Media S.A., 2017)
BackgroundEvery health professional around the world is at risk of blood/body fluid exposure and needle stick/sharp injury as a result of exposure to blood or body fluids and needle or sharp injuries. However, the extent of these hazards and their driving forces are not well documented in Ethiopia. Thus, the aim of this study was to assess determinants of blood/body fluid exposure and needle stick/sharp injury among nurses working in Jimma zone, southwest Ethiopia.MethodsAn institution-based census was conducted among 318 nurses working in Jimma zone public hospitals from March 10 to 30, 2016. Data were collected by using pretested self-administered questionnaire. Epi info and SPSS were used for data entry and analysis, respectively. Descriptive statistics were done. Bivariate and inter multivariate logistic regression analysis was also carried out to identify predictors of occupational hazards.ResultsThe overall prevalence of blood/body fluid exposure and needle stick/sharp injury was found to be 249 (78.3%). Blood/body fluid exposure and needle stick/sharp injury incidents were reported by 62.6 and 58.8% of respondents, respectively. Majority of the hazards occurred during morning shift. Being male [AOR: 2.20, 95% confidence interval (CI): 1.09, 4.4], being single (AOR: 2.26, 95% CI: 1.09, 4.69), and having no training on infection prevention (AOR: 5.99, 95% CI: 3.14, 11.41) were positively associated with blood/body fluid exposure and needle stick/sharp injury; while working in chronic illness follow-up clinic (AOR: 0.19, 95% CI: 0.05, 0.71) showed negative association at p value of 0.05.ConclusionPrevalence of blood/body fluid exposure and needle stick/sharp injury was high among the nurses. The safety of nurses depends directly on the degree to which nurses can identify and control the varied occupational hazards specific to jobs. Thus, working unit specific safety precautions and basic infection prevention in-service training might improve nurses' safety practice and thereby decrease the on job hazard.